PENDIDIKAN KARAKTER DALAM PERKEMBANGAN MORAL PESERTA DIDIK - Novida Dwici Yuanri Manik; Yusak Tanasyah (Sekolah Tinggi Teologi Moriah, 2020)
The development of the times demands the intellectual development of humans to be able to compete in the world of work and in living a life of service. However, there are things that are far more important than just intellectual, such as morals and character. Without good morals, all the knowledge gained will not be able to have a good impact on the world of work and service. Information is important, but the cultivation of good morals needs to be taught as early as possible starting from the family and teachers at school. The concept of Christian ethical philosophy is important to be the philosophical underlying foundation of character and moral education. Everything related to teaching character and morals requires cooperation between educators in the family and school. So it is hoped that the provision of useful information to develop the intellectuals of students, in line with the cultivation and application of Christian and moral character. Perkembangan zaman menuntut perkembangan intelektualitas manusia untuk mampu bersaing di dunia kerja dan dalam menjalani kehidupan yang mengabdi. Namun, ada hal yang jauh lebih penting dari sekedar intelektual, seperti akhlak dan budi pekerti. Tanpa akhlak yang baik, segala ilmu yang didapat tidak akan mampu memberikan dampak yang baik bagi dunia kerja dan pengabdian. Informasi memang penting, namun penanaman akhlak yang baik perlu diajarkan sedini mungkin dimulai dari keluarga dan guru di sekolah. Konsep filsafat etika Kristen penting untuk menjadi landasan filosofis yang mendasari pendidikan karakter dan moral. Segala sesuatu yang berkaitan dengan pengajaran budi pekerti dan akhlak memerlukan kerjasama antara pendidik di lingkungan keluarga dan sekolah. Sehingga diharapkan pemberian informasi yang bermanfaat untuk mengembangkan intelektualitas siswa, sejalan dengan penanaman dan penerapan karakter kristiani dan moral.